2009
DOI: 10.1136/thx.2008.112953
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway function and arousability to ventilatory challenge in slow wave versus stage 2 sleep in obstructive sleep apnoea

Abstract: Patients with obstructive sleep apnoea (OSA) have reduced event rates during slow wave sleep (SWS) compared with stage 2 sleep. To explore this phenomenon, ventilatory and arousal timing responses to partial and complete airflow obstruction during SWS versus stage 2 sleep were examined. Methods Ten patients, mean6SD apnoeaehypopnoea index (AHI) 49.7616.5 events/h with reduced OSA frequency during SWS (SWS AHI 18.9614.0 events/h) slept with an epiglottic pressure catheter and nasal mask/ pneumotachograph. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 38 publications
2
40
2
Order By: Relevance
“…However, a potential mechanism that could lead to an increased phasic EMG GG activity during Stage 3 would be by an increased tolerance to negative pharyngeal pressure (higher arousal threshold) and, consequently, larger reflex muscle activation. (Ratnavadivel, et al, 2010). By matching analyzed breaths for CPAP level and epiglottic pressure, we believe that sleep stage differences in EMG GG were minimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, a potential mechanism that could lead to an increased phasic EMG GG activity during Stage 3 would be by an increased tolerance to negative pharyngeal pressure (higher arousal threshold) and, consequently, larger reflex muscle activation. (Ratnavadivel, et al, 2010). By matching analyzed breaths for CPAP level and epiglottic pressure, we believe that sleep stage differences in EMG GG were minimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is warranted, as current treatments for OSA in both children and adults are often incompletely effective in mitigating sleep-disordered breathing and its consequences, particularly when CPAP compliance is considered. Elevated arousal thresholds in OSA may also be protective via preservation of sleep and facilitation of upper airway muscle activity (8)(9)(10). Thus, it is unclear if elevated arousal thresholds in some patients with OSA are a consequence/adaptive response or a contributor to the disorder.…”
Section: From the Authorsmentioning
confidence: 99%
“…In this issue of Thorax , Ratnavadival et al 21 provide an important insight into several critical questions ( see page ). The authors have observed an increase in arousal threshold to respiratory stimuli in slow wave sleep (SWS) compared with stage 2 non-REM sleep.…”
mentioning
confidence: 99%